'Masters of the Universe': Demystifying Leadership in the Context of the 2008 Global Financial Crisis. (13th January 2015) - Knights, David; McCabe, Darren
<x xml:space="preserve">Abstract</x> There have been numerous explanations of the 2008 global financial crisis, ranging from the greed of the bankers to excessive deregulation due to neoliberalism and the financialization of everything. This paper argues that a discussion of parallels between the crisis and leadership discourses can generate new insights into both. Through an empirical study of the subjectivity of leaders in a UK building society, discourses around both leadership and the crisis are argued to reflect and reproduce similar taken‐for‐granted assumptions about subjectivity and representations of organizational and economic life. These are grounded in the belief that leaders are 'Masters of the Universe', who are able to predict and secure the future. The authors believe that these assumptions and representations contributed to the crisis and are now in danger of producing yet another bubble.